The paradox of creativity. (January 2021) - Bonetto, Eric; Pichot, Nicolas; Pavani, Jean-Baptiste; Adam-Troïan, Jaïs
Abstract: Creativity seems to yield survival and reproductive benefits. Creative behaviors allow individuals to solve problems in new and appropriate ways, and thus to promote their survival. They also facilitate bonding and constitute a signal of one's fitness, favoring attraction of mates. However, to be creative, individuals often have to violate social norms in order to promote change. So far, this deviance induced by creative behaviors had not been seen as an adaptive disadvantage. This deviance entails negative consequences as social exclusion or ostracism, which are detrimental for both survival (e.g., reduced access to resources within the group) and reproduction (reduced reproductive fitness). Thus, the adaptive benefits yielded by creativity have to be nuanced by these potential disadvantages. The paradox of creativity proposes a finer-grained vision of the adaptive reasons why creativity has been maintained within the human species, has evolved, and is collectively regulated. Research perspectives are also proposed. Highlights: Creative behaviors seem to yield survival and reproductive benefits. However, to be creative, individuals often have to violate social norms. This deviance entails consequences detrimental for both survival and reproduction. We propose to call this paradox the paradox of creativity.